Open source in imaging informatics. - Nagy P (Journal of Digital Imaging)
The open source community within radiology is a vibrant collection of developers and users working on scores of collaborative projects with the goal of promoting the use of information technology within radiology for education, clinical, and research purposes. This community, which includes many commercial partners, has a rich history in supporting the success of the digital imaging and communication in medicine (DICOM) standard and today is pioneering interoperability limits by embracing the Integrating the Healthcare Enterprise. This article describes only a small portion of the more successful open source applications and is written to help end users see these projects as practical aids for the imaging informaticist and picture archiving and communication system (PACS) administrator.